"I Just Didn't Feel like a Student Anymore:" Student Responses to Emergency Distance Learning. Issue 3 (27th May 2022) - Tate, Tamara; McPartlan, Peter; Baker, Rachel; Aubele, Joseph; Warschauer, Mark
ABSTRACT: This paper describes the results of surveys and interviews from over 1800 students in five large STEM classes at a research university when classes abruptly moved online for spring quarter 2020 due to the COVID-19 pandemic. We examine how students' expectations compared to their realities at the end of the quarter; what factors impacted their spring 2020 quarter; and students' academic sense of belonging, self-efficacy, cost of engagement, and effort regulation in spring 2020. We contextualize students' experiences of emergency distance learning (EDL) through quantitative comparisons to previous quarters, open survey responses, and interviews. We also examine heterogeneity with respect to race/ethnicity, gender, first-generation college students, and students from low-income families. We find that there are reasons to expect increased achievement gaps post-EDL, but we also find examples of resiliency and improved self-regulated learning that will be life-long assets for students. Our goal in this paper is to use exploratory findings from one particular context to help identify potential ways to disrupt the reproduction and deepening of educational inequality exacerbated by the crisis, and educational opportunities in these unconventional times.